2014
DOI: 10.1111/jfcj.12015
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Biological Processes in Children Associated with High Conflict Parental Divorce

Abstract: Several factors impact a child's adjustment after a parental divorce; a well‐established one is the level of parental conflict during and after a divorce. Research is beginning to investigate the biological mechanisms that may be impacted by childhood trauma in general and parental high conflict specifically. This paper reviews the existing research concerning the relationship between exposure to high parental conflict/trauma and the biological stress response system (the hypothalamic‐pituitary adrenocortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
13
0
3
Order By: Relevance
“…With respect to ongoing interparental conflict, research has consistently shown that exposure to hostility and blocked communication between divorced parents is a major stressor leading to negative outcomes among children (Davidson, O'Hara, & Beck, 2014;Kalmijn, 2016). Conflicts between parents can also entangle grandparents and impede grandparent-grandchild relationships, especially those on the side of a non-residential parent (Westphal, Poortman & van der Lippe, 2015).…”
Section: Variations Within the Group Of Grandchildren With Divorced Parentsmentioning
confidence: 99%
“…With respect to ongoing interparental conflict, research has consistently shown that exposure to hostility and blocked communication between divorced parents is a major stressor leading to negative outcomes among children (Davidson, O'Hara, & Beck, 2014;Kalmijn, 2016). Conflicts between parents can also entangle grandparents and impede grandparent-grandchild relationships, especially those on the side of a non-residential parent (Westphal, Poortman & van der Lippe, 2015).…”
Section: Variations Within the Group Of Grandchildren With Divorced Parentsmentioning
confidence: 99%
“…It has been proposed that ACEs may promote vulnerability to sleep problems through alteration of the hypothalamic-pituitary-adrenal axis resulting from epigenetic changes that occur after continued activation of stress response systems. 16,17 These biological changes are thought to increase vulnerability to stress-related hyper-arousal and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…These findings clearly support the idea of resilience helps children to develop more efficient coping strategies in the process toward higher psychological well-being after overcoming trauma caused by certain marital dissolution-related adversity such as less parental care, more emotional and physical abuse, more emotional neglect, more loneliness, chronic stress, and attachment avoidance and anxiety (Hornor, 2015;Schaan et al, 2019). As adolescents with a high level of resilience are able to adopt effective coping strategies, it will facilitate post-traumatic growth through insight, rumination and self-reflection which would result in a higher level of psychological well-being and reduce the negative consequences following the marital dissolution of their parents (Davidson et al, 2014;Harrington & Loffredo, 2010;Tedeschi & Calhoun, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Schaan et al (2019) illustrated that children and adolescents coming from divorced families might face less parental care, more emotional and physical abuse, more emotional neglect, more loneliness, chronic stress, attachment avoidance, and anxiety. As a consequence, children in the development process to young adults (including adolescence) might experience reduced well-being, resilience, and increased levels of childhood trauma and rejection sensitivity, caused by psychological maladjustment and biological stress response system (in hypothalamicpituitary-adrenocortical axis and the sympathetic nervous system) (Davidson et al, 2014). As mentioned earlier, resilience plays an important role in the healing process from the traumatic experience.…”
mentioning
confidence: 98%